DNA-based association and description of the larval stage of Apatania theischingerorum Malicky 1981 (Trichoptera, Apataniidae), with notes on its ecology - Waringer, Johann; González, Marcos A.; Martín, Luis; Martínez, Jesús; Erzinger, Felicitas; Pauls, Steffen U. (Zootaxa, 2018)
The hitherto unknown larva of Apatania theischingerorum Malicky 1981 is described, based on the association with adult females using sequence data from the mitochondrial cytochrome c oxidase region. Genetic data confirmed the distinct status of this taxon within the parthenogenetic Apatania muliebris complex (Schmid 1954). We provide information on the morphology of the larva and figure the most important diagnostic features. Apatania theischingerorum is morphologically close to A. fimbriata (Pictet 1834). In the context of the Apataniidae key of Waringer et al. (2015), the species pair can be separated by pleural setation patterns on abdominal segment I and by their distribution ranges in Europe: A. fimbriata is known from the Alps, the western and central highlands, the western plains, the Hungarian lowlands and the Carpathians, whereas A. theischingerorum has been recorded exclusively on the Iberian peninsula.